2021
DOI: 10.1111/famp.12710
|View full text |Cite
|
Sign up to set email alerts
|

Online relationship education for help‐seeking low‐income couples: A Bayesian replication and extension of the OurRelationship and ePREP programs

Abstract: Low‐income couples are at increased risk for relationship instability and divorce. In response, online relationship education programs such as ePREP and OurRelationship have been developed to more easily reach this population. A previous trial indicated that these programs promote relationship functioning (Doss et al., 2020) and individual well‐being (Roddy et al., 2020a). However, given that these effects were notably larger than previous studies of in‐person relationship education and approached effect sizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
2
9
1
Order By: Relevance
“…Thus, these results likely suggest that couples with varying levels of these factors experienced similar improvements in coparenting. This is consistent with past studies that showed that the OR program is equally beneficial for couples regardless of their sexual orientation, income, motivation, emotion regulation, relationship status, and military status (Georgia Salivar et al, 2020; Hatch, Knopp, et al, 2021; Hatch, Rothman, et al, 2021; Rothman et al, 2021; Salivar et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, these results likely suggest that couples with varying levels of these factors experienced similar improvements in coparenting. This is consistent with past studies that showed that the OR program is equally beneficial for couples regardless of their sexual orientation, income, motivation, emotion regulation, relationship status, and military status (Georgia Salivar et al, 2020; Hatch, Knopp, et al, 2021; Hatch, Rothman, et al, 2021; Rothman et al, 2021; Salivar et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…To further address this issue, Le et al (2021) evaluated the spillover effects of two online relationship-focused programs on partners’ coparenting in a low-income sample, namely, ePREP and OurRelationship (OR). Both programs have demonstrated notable impacts on various aspects of low-income couples’ romantic relationships in two independent low-income samples (Doss, Knopp, et al, 2020; Hatch, Knopp, et al, 2021). The OR program has also been shown to reduce coparenting conflict in a nationally representative sample (Doss, Knopp, et al, 2020).…”
mentioning
confidence: 99%
“…When the 2 programs were compared, only one significant effect emerged; those in the OurRelationship program experienced greater decreases in communication conflict when compared with those in the ePREP program (Cohen d =−0.24) [ 17 ]. These findings were later reproduced in an independently collected sample [ 25 ].…”
Section: Introductionmentioning
confidence: 79%
“…Significantly, online programs reach more couples within the comfort of their environment (Doss et al, 2020), effectively reducing barriers associated with in‐person interventions, such as work obligations, childcare responsibilities, and transportation constraints (Stanley et al, 2020). Additionally, online platforms offer a solution for reaching low‐income couples and disadvantaged communities, often at a heightened risk for relationship instability and divorce (Doss et al, 2020; Hatch et al, 2022). The Global COVID‐19 pandemic compelled many couples to rely on virtual services (Stanley & Markman, 2020).…”
Section: Introductionmentioning
confidence: 99%